Konstitusionalitas Perlindungan Hukum Terhadap Kebebasan Beragama dan Beribadah di Indonesia - Razak, Askari; A. Sakti R.S. Rakia; A. Darmawansya (JUSTISI, 2022)
In the explanation of Law no. 1/PNPS/1965 stated that the recognized religions in Indonesia are Islam, Christianity, Catholicism, Hindu Buddhism, and Confucianism. As a result, other beliefs loses its legal standing and legal protection by the state. The issue of religious freedom is also influenced by the different interpretations of the terms "religion" and "belief" by the public and law enforcer. First, the terms "religion" and "belief" have different meanings. "Religion" refers to the religions adopted by Indonesian citizens, in accordance with the explanation in Law no. 1/PNPS/1965. While the term "belief" has no legal basis. Second, the terms "religion" and "belief" have identical meanings. If this opinion is recognized, then there will be generalization between "agama wahyu", and "agama budaya”. On the other hand, Article 29 paragraph (2) of the 1945 Constitution of the Republic of Indonesia does not yet have an adequate constitutional interpretation in resolving this issue.